Centralized Adaptive Governance for Curriculum Development in Islamic Education under Society 5.0 - Misbahul Arifin; Muhammad Ilzamul Khoir; Achmad Zahri N.A (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
This study examines how curriculum governance is enacted in Islamic education amid digital transformation in the Society 5.0 era. While existing literature emphasizes digital leadership and technological integration, limited attention has been given to how curriculum governance mediates the relationship between innovation and value-based education. Addressing this gap, the study investigates managerial processes, contextual constraints, and adaptive strategies in a madrasah undergoing curriculum restructuring. A qualitative case study design was employed, involving semi-structured interviews, participant observation, and document analysis. Data were analyzed using a thematic approach supported by QualCoder 3.8, enabling systematic coding and pattern identification across data sources. The findings reveal a governance paradox: curriculum management is structurally coherent yet operationally uneven. Strong leadership ensures alignment with Islamic values through centralized planning, implementation, and evaluation. However, adaptation to digital demands is mediated by disparities in teacher readiness, infrastructural limitations, and weak parent–school linkages. Consequently, curriculum implementation is adaptive but fragmented across instructional contexts. This study offers a novel contribution by reconceptualizing curriculum governance as centralized adaptive governance, demonstrating that adaptation in value-based educational systems is mediated through hierarchical structures rather than driven by decentralization. The findings extend curriculum and digital leadership literature by highlighting the need to balance institutional coherence with distributed pedagogical capacity.